Manganese oxide thin film using aerosol assisted chemical vapour deposition (AACVD) technique for solar energy harvesting / Khadijah Hamzah - Hamzah, Khadijah (2020)
The demand for renewable and clean energy has resulted in the rapid development of its technology. One of the ways to generate energy from natural sunlight is by using a photoelectrochemical cell. Currently, the race is on to find the most suitable and most efficient material for the semiconductor electrode of the photoelectrochemical cell. This research is focused on the study of Manganese oxide material deposited using the AACVD technique, with Mn2O3-4TiO2 thin film and Mn2O3-Co2O3-TiO2 thin film deposited using the technique within a specific range of time and temperature. AACVD technique had been chosen because of its ability to produce high quality thin film by using a simple method, with various compositions and has low production cost. The first objective was to define the highest light absorption level by varying the temperature and time during the AACVD process for manganese oxide thin film. The characterization of the material analyses was carried out using XRD, Raman and FESEM. A UV-Vis machine was used to define the material’s optical band gap using Tauc plot. The photocurrent density recorded using photoelectrochemical test was 2.5 mA/cm2 and 4.91 mA/cm2 respectively for Mn2O3-4TiO2 thin film and Mn2O3-Co2O3-TiO2 thin film. The photoconversion efficiency was 0.95% for Mn2O3-4TiO2 thin film and 2.82% for Mn2O3-Co2O3-TiO2 thin film. This concluded the improvement on photocurrent density and efficiency compared to previous studies.